Emergent Literacy A Developmental Perspective of Literacy - Bahuguna, Pooja (JOURNAL OF INDIAN EDUCATION, 2022)
Seeing literacy (including early reading) from a developmental perspective is a great achievement. It has not only contributed in the formulation of readingwriting instructions from a child-centred perspective but also has given the world a perspective which believes that preschool literacy experiences are equally valuable. The purpose of this paper is to bring forth the significance of developmental and holistic nature of literacy by reviewing the researches on two contrasting views: Reading Readiness Perspective and Emergent Literacy Perspective. The paper also interprets developmental perspective of literacy in the light of Vygotskian theory of literacy and development and Marie Clay’s contribution in early literacy. Early literacy in Indian context is also reviewed in the light of emergent literacy framework in the later section of this paper.